2022
DOI: 10.3390/met12020192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Parameters on Strength and Corrosion Resistance of Friction Stir-Welded AA6082

Abstract: The friction stir welding method is increasingly attracting interest in the railway sector due to its environmental friendliness, low cost, and ease of producing high-quality joints. Using aluminum alloys reduces the weight of structures, increasing their payload and reducing fuel consumption and running costs. The following paper presents studies on the microstructure, strength, and corrosion resistance of AA6082 aluminum alloy sheets joined via friction stir welding. The sheets were joined by employing two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Due to the different behaviors of these alloys under deformation and temperature, differences in the hardness profile on the advancing and retreating sides can be observed. Analyzing the hardness profile from the side of the AA6060 alloy to the center of the joint, the typical shape of the hardness profile for FSW joints of 6xxx-T6 series aluminum alloys is maintained, characterized by a minimum of hardness in the heat-affected zone [26,27]. Softening observed in the heat-affected zone on the side of AA6060-T6 is an effect of precipitate coarsening and dissolution, due to sufficient heat input.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the different behaviors of these alloys under deformation and temperature, differences in the hardness profile on the advancing and retreating sides can be observed. Analyzing the hardness profile from the side of the AA6060 alloy to the center of the joint, the typical shape of the hardness profile for FSW joints of 6xxx-T6 series aluminum alloys is maintained, characterized by a minimum of hardness in the heat-affected zone [26,27]. Softening observed in the heat-affected zone on the side of AA6060-T6 is an effect of precipitate coarsening and dissolution, due to sufficient heat input.…”
Section: Resultsmentioning
confidence: 99%
“…AA6351 is an aluminum alloy that has been developed as a high-strength material with good corrosion resistance. This alloy contains silicon, magnesium, and manganese as its main alloying elements, and often used in applications where high strength and good corrosion resistance are required, such as in the construction of aircraft and aerospace components, marine applications as structural components [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Laska et al observed in friction stir welded joints of AA6082 alloys that the best corrosion behavior in NaCl 3.5% solution was obtained with the highest revolutionary pitch (between 6.0 and 6.5 rev•mm −1 ) [45]. Souza et al studied localized corrosion resistance in friction stir welded joints of AA2198-T8 alloys.…”
Section: Introductionmentioning
confidence: 99%